DNA methyltransferase CHROMOMETHYLASE3 prevents ONSEN transposon silencing under heat stress. - Kosuke Nozawa (Public Library of Science (PLoS), 2021)
DNA methylation plays crucial roles in transposon silencing and genome integrity. CHROMOMETHYLASE3 (CMT3) is a plant-specific DNA methyltransferase responsible for catalyzing DNA methylation at the CHG (H = A, T, C) context. Here, we identified a positive role of CMT3 in heat-induced activation of retrotransposon ONSEN. We found that the full transcription of ONSEN under heat stress requires CMT3. Interestingly, loss-of-function CMT3 mutation led to increased CHH methylation at ONSEN. The CHH methylation is mediated by CMT2, as evidenced by greatly reduced CHH methylation in cmt2 and cmt2 cmt3 mutants coupled with increased ONSEN transcription. Furthermore, we found more CMT2 binding at ONSEN chromatin in cmt3 compared to wild-type accompanied with an ectopic accumulation of H3K9me2 under heat stress, suggesting a collaborative role of H3K9me2 and CHH methylation in preventing heat-induced ONSEN activation. In summary, this study identifies a non-canonical role of CMT3 in preventing transposon silencing and provides new insights into how DNA methyltransferases regulate transcription under stress conditions.